SISTEM INFORMASI AKADEMIK PADA MADRASAH ALIYAH PONDOK PESANTREN KARYA PEMBANGUNAN AL – HIDAYAH PROVINSI JAMBI - lucy simorangkir; Meki Febriansyah (LP2M Universitas Nurdin Hamzah, 2026)
This study aims to design and develop a web-based Academic Information System (SIAKAD) at Madrasah Aliyah Pondok Karya Pembangunan Al-Hidayah, Jambi Province, to replace the manual process of academic data management. The system was developed to support the management of student biodata, grades, class schedules, attendance, and academic reporting in a more effective and efficient manner. System requirements include user data management, access rights control, grade and attendance input, schedule management, and automated academic report generation. The system was developed using the Laravel framework based on PHP with a Model–View–Controller (MVC) architecture and MySQL database. The development method applied was the iterative System Development Life Cycle (SDLC), which includes the stages of requirements analysis, design, coding, and repeated testing according to user needs. System testing was conducted using Black Box Testing to ensure that all functions operated according to specifications, as well as User Acceptance Testing (UAT) to evaluate the level of user acceptance in terms of usability, accessibility, and feature suitability. The results of the study indicate that the implementation of the Academic Information System improved the efficiency, accuracy, and security of academic data management. The system is equipped with security features such as protection against SQL Injection, Cross-Site Scripting (XSS), and Cross-Site Request Forgery (CSRF), and also provides instant reporting features in PDF and Excel formats. Therefore, the system serves as an effective solution to support the digitalization of academic administration in the madrasa environment